Modelling asymmetric two-port reciprocal microwave structures by means of compact equivalent circuits - Abdo-Sánchez, María Elena; Martín-Guerrero, Teresa María; Esteban Marzo, Jaime; Camacho-Peñalosa, Carlos (My University, 2019)
Effective microwave systems design requires powerful and reliable modeling techniques. Today modern CAD tools provide such support from device physics to circuit level or from electromagnetics to system level. Nevertheless, affordable and handy tools capable of providing a first approach on the evaluation of the main parameters that govern system performance are required in the first stage of almost any design. The authors have extensive experience in the design of reconfigurable Leaky Wave Antennas (LWAs) for microwave applications, and an essential tool in their design procedure has been the use of compact equivalent circuits for the radiators that constitute these antennas [1]. In previous works, lattice-network based equivalent circuits have demonstrated to be extremely useful to perform parametric studies or preliminary performance estimation of such LWAs, by means of fully or quasi-analytical calculations. Latticenetwork equivalent circuits also have interesting features such as their guaranteed realizability and the orthogonal mode decomposition, which facilitates the physical insight into the modelled structure.
Keywords: Fotones -- Congresos; Electromagnetismo -- Congresos; Congresos y conferencias; equivalent circuit; microwave; lattice-network